A chemical study of the coloring matters of Curcuma longa Linne (Family Zingiberaceae) - Talusan, Elizabeth G.
Orange-yellow crystalline powder was isolated from the air-dried, powdered rhizomes of Curcuma longa L. m.p. 178-183. Thin layer chromatography of the benzene extract gave three major components and to minor components. The first and second spots, having Rf values of 0.16 and 0.28 respectively, are closely related to curcumin, the major coloring matter of Curcuma longa L. Spectrophotometric analyses were also made.